2016
DOI: 10.1016/j.sdentj.2015.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Fracture resistance of endodontically treated teeth restored with indirect composite inlay and onlay restorations – An in vitro study

Abstract: Within the limitations of this study, endodontically treated teeth were successfully restored with indirect composite inlay and onlay restorations. However, the fractures that accompanied the inlay restorations were more severe and were unable to be restored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 36 publications
2
24
0
2
Order By: Relevance
“…Comparison of fracture strength of restorations with that of sound teeth was out of the scope of this study. Moreover, some previous studies on compressive strength of sound teeth reported value, which were similar to the value in the group with 2.5 mm cusp coverage in our study ( 30 ). Therefore, there was no need to use sound premolar teeth as a control group in our study.…”
Section: Discussionsupporting
confidence: 91%
“…Comparison of fracture strength of restorations with that of sound teeth was out of the scope of this study. Moreover, some previous studies on compressive strength of sound teeth reported value, which were similar to the value in the group with 2.5 mm cusp coverage in our study ( 30 ). Therefore, there was no need to use sound premolar teeth as a control group in our study.…”
Section: Discussionsupporting
confidence: 91%
“…With good values of mechanical properties, they started to be indicated for inlays, onlays, crowns and fixed partial denture [6,7]. Currently, ICR's are an excellent aesthetic alternative to ceramic due to the facility of their manufacture in the laboratory [4,6], polymerization outside the mouth [8] and more dental preservation [9].…”
Section: Introductionmentioning
confidence: 99%
“…This mathematical methodology consists in the evaluation of stress distribution trougth structures. Currently, several studies with this purpose take into consideration parameters of occlusal force and use of mesial-occlusal-distal preparations (MOD) in premolars [3,7,11]. When submitted to an occlusal load, the type of restorative material was shown to affect the deflection of the cusps [3].…”
Section: Introductionmentioning
confidence: 99%
“…Improved adhesion occurs due to the exposure of a bigger surface area associated with better prisms orientation and removal of weakened enamel (Carvalho et al, 2000;Mizuno et al, 2015;Schneider, Messer, & Douglas, 1981;Veneziani, 2017;Wang et al, 2018). In some situations, the bevel can also promote cusp splinting in extensive posterior restorations, reducing the risk of catastrophic fractures, similar to an onlay restoration with cusp coverage (Alshiddi & Aljinbaz, 2016;Mondelli, Ishikiriama, de Oliveira Filho, & Mondelli, 2009;Soares, Santos-Filho, Martins, & Soares, 2008). Nevertheless, prisms orientation are variable through the occlusal surface and such variations can generate doubts about the necessity of beveling the cavosurface angle, especially in wider cavities, which presents a lower fracture resistance and in which the integrity of restoration's margins is challenging to be achieved (Giorgi et al, 2014;Soliman et al, 2016;Veloso et al, 2018), especially because some reports show no improvement in cavities with bevel, resulting in an unnecessary cavity overextension (Mahn et al, 2015;Soliman et al, 2016).…”
Section: Introductionmentioning
confidence: 99%